Readiness assessment method based on the reference architecture model for industry 4.0 - RAMI 4.0 - Bastos, Alan (2021)
The Industry 4.0 concept inception definitively provided a disruptive glimpse in terms of possibilities in a multidisciplinary spectrum. The convergence and synergy from technologies generated quite high expectations. In terms of advancements, the efficiency increase is one of the key factors. Smart factories must be capable of producing more and in an ecologically cleaner manner, by benefiting from less environmentally impacting energy sources. The present moment is for digital transformation in the diverse enabling transverse areas. For that to be feasible, the next steps are towards standardization, which brings viability to expand and integrate the assorted devices and processes, bringing intelligence closer to all the involved equipment by capitalization. The gap that this research aims to explore is in the assessment of the ongoing industries, focusing on the current status of the operational plants technologically. In other words, by mapping the present, as-is, situation, the stakeholders obtain a valuable guidance resource to go through the journey upon permeating the Industry 4.0 status, the greater objective. Undoubtedly, a path of considerable length, but with well-proportioned outcomes. The solution’s ambition is to rate, grade, and calculate the readiness levels of the institution accordingly to that scope. To achieve that, methods will be developed and applied to gather information and subsequently treat it. Finally, the results will be presented according to the fourth industrial revolution preconized capabilities, as defined by the Rami 4.0 Reference Architecture Model. Having presented the information, there is a possibility to establish a road-map to achieve the desired level.